The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.2165/11310770-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Etanercept in Psoriasis after Switching from Other Treatments

Abstract: Since targeted biologic treatments have been introduced for the treatment of plaque-type psoriasis and psoriatic arthritis, switching between different medications has become necessary in selected patients, particularly after treatment failures. To evaluate the efficacy and safety of etanercept treatment in adult patients with psoriasis after failure to respond to other previous therapies. In particular, the differences in efficacy profiles after switching from traditional (cyclosporine [ciclosporin], methotre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
62
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(67 citation statements)
references
References 10 publications
1
62
0
Order By: Relevance
“…The clinical benefits of etanercept are well established with regard to peripheral joint disease and skin symptoms 17,20,21,22,23,29 . Thus, in pivotal trials, 12-week treatment with etanercept led to significant increases, relative to placebo, in the proportion of patients with PsA achieving the PsARC and PASI 75-level skin clearance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The clinical benefits of etanercept are well established with regard to peripheral joint disease and skin symptoms 17,20,21,22,23,29 . Thus, in pivotal trials, 12-week treatment with etanercept led to significant increases, relative to placebo, in the proportion of patients with PsA achieving the PsARC and PASI 75-level skin clearance.…”
Section: Discussionmentioning
confidence: 99%
“…Etanercept discontinuation because of safety concerns has occurred rarely 19,30,37 or not at all 29,36 in available studies, although British patient registry data suggested that about 3% of patients discontinued etanercept per year, citing AE 38 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, in patient 8, switching to etanercept after previous TNF-antagonist failure was not successful. Although etanercept may represent an effective and well-tolerated alternative treatment for psoriasis patients who have failed to respond to other therapies (traditional or biologic), it has been reported that etanercept was more effective in biologic naive patients [20]. However, the rate of response to a second TNF antagonist is usually inferior to that of the first [16].…”
Section: Discussionmentioning
confidence: 99%
“…Data pertaining to patients with psoriasis who switch from one TNF-a antagonist to another, however, have been limited generally to small studies. [14][15][16][17][18][19][20] In the current study, the efficacy of this alternative treatment paradigm was evaluated by assessing clinical response in patients with plaque psoriasis who switch to infliximab after having an inadequate response (IR) to etanercept.…”
Section: Limitationsmentioning
confidence: 99%